Inhibition of Cpt1a alleviates oxidative stress-induced chondrocyte senescence via regulating mitochondrial dysfunction and activating mitophagy. (July 2022) - Jiang, Ning; Xing, Baizhou; Peng, Rong; Shang, Jie; Wu, Biao; Xiao, Peilun; Lin, Shiyuan; Xu, Xianghe; Lu, Huading
Abstract: Osteoarthritis (OA) is an age-related chronic degenerative disease, and chondrocyte senescence has been established to play an important role in the pathological process. There is ample evidence to suggest that lipid metabolism plays an important role in the aging process. However, the effect of lipid metabolism on chondrocyte senescence and OA remains unclear. Accordingly, we constructed a TBHP-induced senescent chondrocytes model and a destabilization of the medial meniscus (DMM) mouse model. We found that lipid accumulation and fatty acid oxidation were enhanced in senescent chondrocytes. Interestingly, carnitine palmitoyltransferase 1A (Cpt1a), the rate-limiting enzyme for fatty acid oxidation, was highly expressed in senescent chondrocytes and murine knee cartilage tissue. Suppressing Cpt1a expression using siRNA or Etomoxir, an inhibitor of Cpt1a, could attenuate oxidative stress-induced premature senescence and OA phenotype of primary murine chondrocytes, decrease cellular ROS levels, restore mitochondrial function, and maintain mitochondrial homeostasis via activating mitophagy. In vivo, pharmacological inhibition of Cpt1a by Etomoxir attenuated cartilage destruction, relieved joint space narrowing and osteophyte formation in the DMM mouse model. Overall, these findings suggested that knockdown of Cpt1a alleviated chondrocyte senescence by regulating mitochondrial dysfunction and promoting mitophagy, providing a new therapeutic strategy and target for OA treatment. Highlights: Abnormal lipid metabolism and fatty acid oxidation were enhanced in oxidative stress induced senescence of chondrocytes. Cpt1a knockdown alleviated the cellular senescence phenotype and maintained chondrocyte homeostasis. Cpt1a knockdown suppressed chondrocyte senescence by inhibiting mitochondrial dysfunction and enhancing mitophagy. Pharmacological inhibition of Cpt1a alleviated the progression of OA.